2016
DOI: 10.5194/angeo-34-917-2016
|View full text |Cite
|
Sign up to set email alerts
|

Proton and heavy ion acceleration by stochastic fluctuations in the Earth's magnetotail

Abstract: Abstract. Spacecraft observations show that energetic ions are found in the Earth's magnetotail, with energies ranging from tens of keV to a few hundreds of keV. In this paper we carry out test particle simulations in which protons and other ion species are injected in the Vlasov magnetic field configurations obtained by Catapano et al. (2015). These configurations represent solutions of a generalized Harris model, which well describes the observed profiles in the magnetotail. In addition, three-dimensional ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…We can see that CS is well ordered with . Clearly, this is due to the fact that is proportional to the Larmor radius (see also trajectories in Figure 15 of Kronberg et al, 2014 and in Figure 5 of Catapano et al, 2016). Therefore, ions that spend a long time in the CS interact many times with the random fluctuations and undergo a Fermi-like process, thus developing the power law tail.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We can see that CS is well ordered with . Clearly, this is due to the fact that is proportional to the Larmor radius (see also trajectories in Figure 15 of Kronberg et al, 2014 and in Figure 5 of Catapano et al, 2016). Therefore, ions that spend a long time in the CS interact many times with the random fluctuations and undergo a Fermi-like process, thus developing the power law tail.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…• Test particle simulations of the acceleration of different ion species by stochastic fluctuations in the Earth's magnetotail are performed • For the top 10% energetic ions, the energy gain grows almost linearly with the ion charge, while the dependence on the ion mass is weaker • We propose that the possible presence of O 5+∕6+ ions may contribute to explain the strong oxygen energization observed in the magnetotail 10.1002/2017GL075092 has been pointed out by Ono et al (2009) andNosé et al (2014). Recently, Catapano et al (2016) studied the acceleration of H + , He + , and O + while varying the equilibrium magnetic field profile and the intensity of the perturbations. Also, high charge state ions are observed in the magnetosphere (Kremser et al, 1987).…”
Section: 1002/2017gl075092mentioning
confidence: 89%
See 2 more Smart Citations
“…There are many acceleration mechanisms responsible for the ion energization in the magnetotail. These include adiabatic processes, such as first Fermi and betatron acceleration, as well as nonadiabatic processes, such as (1) large-scale convection electric field during "demagnetization" 10.1029/2019JA026553 near the current sheet center (e.g., Lyons & Speiser, 1982) and (2) inductive electric fields generated during transient processes such as the formation of a magnetic X-line (e.g., Luo et al, 2014;Wygant et al, 2005), dipolarization fronts (e.g., Delcourt & Sauvaud, 1994;Greco et al, 2015), plasmoids (e.g., Zong et al, 1997), and electromagnetic turbulence (e.g., Catapano et al, 2016) as shown for the terrestrial magnetosphere.…”
Section: Introductionmentioning
confidence: 99%